Exercise and use of enhancement drugs at the time of the COVID-19 pandemic: A multicultural study on poping strategies during self-Isolation and related risks - Dores, Artemisa Rocha (2021)
Little is known about the impact of restrictive measures during the COVID-19 pandemic on self-image and engagement in exercise and other coping strategies alongside the use of image and performance-enhancing drugs (IPEDs) to boost performance and appearance.